Manufacturing method using negative electrode material based on pre-lithiation and carbon-coated silicon and photoelectromagnetic energy irradiation

Through powder drying and photoelectromagnetic energy application, the active substances in the lithium secondary battery are encapsulated and prelithiated, solving the problem of electrode loss caused by volume expansion and achieving efficient battery performance improvement.

CN119895588APending Publication Date: 2025-04-25VITZROCELL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380065360.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-16
Filing Date
2023-08-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the problems of electrode integrity and electrical insulation losses caused by volume expansion of active substances in lithium secondary batteries. At the same time, the existing prelithiation process is complex and costly.

Method used

The negative electrode with high volume expansion rate of silicon is encapsulated and prelithiated with active substances, and the high-volume expansion rate is used to achieve efficient heat transfer and carbonization process using strong pulse light or microwave.

Benefits of technology

Prelithiation of active substances and encapsulation is achieved, a solid housing with electrical conductivity and structural support is provided, reducing the damage to the electrodes by volume expansion, and improving the initial Coulomb efficiency and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119895588A_ABST
    Figure CN119895588A_ABST
Patent Text Reader

Abstract

Disclosed are a method for manufacturing a negative electrode material for a lithium secondary battery using pre-lithiation and photoelectromagnetic energy irradiation, and a negative electrode material for a lithium secondary battery. The method includes the steps of: mixing an active material, a polymer, and a lithium salt in a solvent to form a liquid mixture; performing powder drying on the liquid mixture; and applying photo-electromagnetic energy to the product after the powder drying.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for manufacturing a negative electrode material for lithium secondary batteries such as lithium ion batteries, lithium metal batteries, lithium sulfur batteries and lithium air batteries. In particular, the present invention relates to a method for manufacturing a negative electrode material for lithium secondary batteries that can pre-lithiate and encapsulate active materials by irradiating with photo-electromagnetic energy.

[0002] Furthermore, the present invention relates to a pre-lithiated and encapsulated negative electrode material for a lithium secondary battery. Background Art

[0003] Lithium secondary batteries, such as lithium-ion batteries, are used in a wide range of applications, from small, portable electronic products to large electric vehicles, and their demand is increasing. As the shift from fossil fuel vehicles to electric vehicles becomes more widespread, the focus on high-performance lithium secondary batteries is also increasing. In order to achieve higher capacity, longer life, faster charging speed and more reliable safety of lithium secondary batteries, many studies are being conducted, one of which is to develop electrodes using active materials with higher energy density than existing materials.

[0004] Silicon (Si) is considered a strong candidate for active material for negative electrodes of lithium batteries due to its theoretical capacity of up to 3600 mAh / g and high energy density. However, it is widely known that silicon has a high volume expansion rate during repeated lithiation processes. This drastic volume change can lead to the pulverization and peeling of active materials, resulting in loss of electrode integrity and electrical insulation, which reduces battery performance.

[0005] In order to solve the problem related to the volume expansion rate of such active materials, some solutions have been proposed. For example, the active material can be encapsulated with a strong outer shell to suppress the volume change of the active material or provide sufficient space to reduce the impact of physical stress during the charge and discharge cycle.

[0006] In some existing literature, nanoporous structures are generated on the active material or the shell surrounding the active material to increase the reaction surface area, thereby making ion diffusion easier. However, this technology is accompanied by high economic or environmental costs in terms of process, which ultimately increases the production cost of battery products.

[0007] Moreover, compared with graphite-based negative electrode materials, silicon-based negative electrode materials have a lower initial efficiency because lithium ions are lost in an irreducible state after reacting on the silicon surface. In order to solve this problem, a pre-lithiation method is proposed, but the prior art is to perform pre-lithiation after coating and drying the negative electrode slurry to avoid reactions with binders or graphite and other substances in the slurry, so a more complicated process is required. Moreover, this process divides the encapsulation of silicon and the subsequent pre-lithiation process into two stages, which increases the complexity of the overall process. Summary of the invention Technical issues

[0008] The problem to be solved by the present invention is to provide a method for manufacturing a negative electrode material for a lithium secondary battery, which can pre-lithiate and encapsulate an active material.

[0009] Furthermore, the problem to be solved by the present invention is to provide a pre-lithiated and encapsulated negative electrode material for a lithium secondary battery. Technical Solution

[0010] In order to solve the above problems, the method for manufacturing negative electrode materials for lithium secondary batteries of the present invention encapsulates and pre-lithiates the negative electrode active material with a high volume expansion rate such as silicon. In the present invention, powder drying and photoelectromagnetic energy application are used simultaneously. The photoelectromagnetic energy that can be used in the present invention includes intense pulsed light (IPL) or microwaves. Both intense pulsed light and microwaves simplify the heat transfer process, and compared with traditional heating methods, heat loss is less, and high energy can be transferred in a short time.

[0011] More specifically, the method for manufacturing negative electrode materials for lithium secondary batteries according to an embodiment of the present invention includes the following steps: mixing active substances, polymers and lithium salts in a solvent to form a liquid mixture; drying the liquid mixture into powder; and applying photoelectromagnetic energy to the powder drying product to pre-lithiate the active substances and carbonize at least a portion of the polymer.

[0012] In the photoelectromagnetic energy application, the intense pulsed light application is achieved by irradiating high-power xenon-light with a wavelength range of 500nm to 1200nm. On the other hand, the carbonization effect of the polymer may be different depending on the application time of the intense pulsed light. For example, if the application time of the intense pulsed light is within a few milliseconds, the carbonization effect is mainly concentrated on the outside of the shell, presenting a shell structure including a hard carbonized outer shell and a soft inner shell in the state of the inner polymer. For example, if the application time of the intense pulsed light is more than 10 milliseconds, the polymer is carbonized as a whole, and the whole may present a shell formed by carbon. The carbonized outer shell or the carbonized shell can provide conductivity and structural support along the solid electrolyte interface (SEI). The inner layer of the soft polymer is elastic, providing space for the volume expansion of the active material without being crushed.

[0013] For microwave application, depending on the power or time, a shell that is only partially carbonized or completely carbonized can be formed. Microwaves refer to photoelectron waves with a wavelength range of 1mm to 1000mm, which directly increase the temperature of an object by dipolar polarization or interfacial polarization or indirectly transfer heat by plasmatizing the surrounding of the material.

[0014] The heat generated during the polymer carbonization process based on intense pulsed light or microwave application can promote the reaction of lithium salts with silicon, thereby lithiating silicon.

[0015] The active material may include at least one of silicon and silicon oxide.

[0016] The active material may be pre-surface treated by applying photo-electromagnetic energy. The pre-surface treatment may burn impurities contained in the active material in a short time, may form a stable oxide layer on the surface of the active material, and may improve wettability to the electrolyte by changing the surface energy of the active material.

[0017] The lithium salt may include Li 2 O, LiOH, LiO 2 CH, Li 2 CO 3 , Li 2 C 2 O 4 , Li 3 C 6 H 5 O 7 、LiNO 3 , LiCl, LiF or lithium citrate (Li 3 H 6 H 5 O 7 ) and the like.

[0018] The solvent may include an aqueous solvent or an organic solvent.

[0019] The step of drying the powder may include the following steps: spraying the liquid mixture into an air suspension chamber to generate liquid droplets; and circulating and drying the liquid droplets in the air suspension chamber using a heater.

[0020] Photo-electromagnetic energy may also be applied within the air suspension chamber to accelerate the drying process, carbonization, and pre-lithiation.

[0021] In another embodiment, the step of drying the powder may include the following steps: spraying the liquid mixture into a chamber to generate droplets; rapidly freezing the droplets into frozen powder in the chamber using nitrogen; and vacuum drying the frozen powder.

[0022] The negative electrode material for a lithium secondary battery in an embodiment of the present invention for solving the above-mentioned problem comprises: a lithiated active material; and a shell layer, which surrounds the lithiated active material and is formed with pores, wherein the lithiated active material comprises a lithium-silicon alloy and a lithium silicate layer surrounding the lithium-silicon alloy, and the outermost side of the shell layer is formed by carbon. Effects of the Invention

[0023] The present invention provides a novel method for encapsulating active materials by pre-lithiation and photo-electromagnetic energy irradiation. According to the method for manufacturing negative electrode materials for lithium secondary batteries of the present invention, pre-lithiation and encapsulation of active materials can be achieved simultaneously by photo-electromagnetic energy irradiation.

[0024] Furthermore, in this way, according to the method for manufacturing negative electrode materials for lithium secondary batteries of the present invention, a strong protective shell with conductivity can be provided, and pre-lithiation can be performed in the state of powdered negative electrode material before manufacturing the negative electrode by pre-lithiation before active material encapsulation.

[0025] In particular, in the present invention, since it is a pre-lithiated negative electrode active material, the effect of improving the initial columbic efficiency (ICE) can be obtained when assembling the battery. It can increase the energy density of the battery by minimizing the amount of negative electrode consumed due to irreversible capacity, reducing the negative electrode ratio during design, and increasing the capacity. The silicon oxide film that can be found in silicon exposed to the air changes to a lithium silicate film, which can prevent the lithiated silicon from producing unnecessary chemical reactions in the subsequent negative electrode and battery manufacturing processes. The shell formed by solid carbon will cover the volume of the active material expanded by lithium, and will not break due to the expansion of silicon during the subsequent charge and discharge process. Since it is not a mixed graphite-silicon negative electrode state, there is no need to consider the oxidation of graphite or the breakage of the carbon chain as in the existing method, nor is there a need to use a lithium solution that does not react with graphite, has a complex manufacturing process and is expensive. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] With reference to the accompanying drawings, several embodiments of the present invention are shown in detail by way of example and not by way of limitation.

[0027] Figure 1 The method for producing the negative electrode material for a lithium secondary battery of the present invention is briefly described.

[0028] Figure 2 An example of the electrospray method is briefly shown.

[0029] Figure 3 A process for drying an active substance encapsulated in powder form in an air suspension chamber using an infrared (IR) heater is shown.

[0030] Figure 4 An example of applying intense pulsed light (IPL) to an active substance encapsulated in powder form within an air suspension chamber is schematically shown.

[0031] Figure 5 The charge and discharge process of the negative electrode material for a lithium secondary battery of the present invention is briefly shown.

[0032] Figure 6 An example of an apparatus for drying an active substance encapsulated in a powder form using a spray freeze drying method is briefly shown. DETAILED DESCRIPTION

[0033] The following description and the embodiments described herein are provided as examples of the principles of various embodiments of the present invention. These embodiments are only used to illustrate these principles and various embodiments, and are not intended to limit the present invention. Throughout the specification and drawings, similar parts are given the same reference numerals. The drawings are not necessarily drawn to scale, and in some cases, the proportions may be exaggerated in order to more clearly describe specific features.

[0034] The present invention provides a method for manufacturing a negative electrode material for a lithium secondary battery, that is, it is possible to minimize the negative side effects such as volume change or high internal stress, cracking, crushing, peeling, electronic insulation of a conductive agent, SEI instability, and electrolyte consumption and battery energy capacity loss caused by the negative electrode of a lithium secondary battery such as a lithium ion battery, a lithium metal battery, a lithium air battery, a lithium sulfur battery or a lithium all-solid-state battery.

[0035] Furthermore, the method for manufacturing negative electrode materials for lithium secondary batteries of the present invention encapsulates negative electrode active materials with a large volume expansion coefficient such as silicon and pre-lithiates them. In the present invention, powder drying and photoelectromagnetic energy application are simultaneously utilized.

[0036] Figure 1 The method for producing the negative electrode material for a lithium secondary battery of the present invention is briefly described.

[0037] Reference Figure 1 The method for manufacturing a negative electrode material for a lithium secondary battery of the present invention comprises: a liquid mixture forming step; a powder drying step; and a step of pre-lithiation and polymer carbonization by applying photoelectromagnetic energy.

[0038] In the liquid mixture forming step, the active material 110 , the lithium salt 120 , and the polymer 130 are mixed in a solvent to form a liquid mixture.

[0039] The liquid mixture used in the method for manufacturing an electrode for a lithium secondary battery of the present invention comprises an active material, a lithium salt, a polymer and a solvent. Exemplarily, relative to 100 parts by weight of solid components other than the solvent in the liquid mixture, 80 to 95 parts by weight of active materials, 1 to 10 parts by weight of lithium salts, and 1 to 10 parts by weight of polymers may be included, and the content of active materials, lithium salts and polymers may vary depending on the type of material used. On the other hand, the solvent may be used in an appropriate amount according to the type of polymer used, for example, relative to 100 parts by weight of solid components, 50 to 100 parts by weight of solvents may be used.

[0040] The solvent may include aqueous solvents (such as water, methanol, ethanol, etc.) and organic solvents. 2 O will become LiOH in water, but will be Li 2 The organic solvent can also prevent a portion of silicon from being rapidly oxidized in the water solvent and producing hydrogen.

[0041] The lithium salt may include Li 2 O, LiOH, LiO 2 CH, Li 2 CO 3 , Li 2 C 2 O 4 , Li 3 C 6 H 5 O 7 、LiNO 3 , LiCl, LiF or one or more lithium-functionalized polymers.

[0042] The active material may include at least one of silicon and silicon oxide.

[0043] The active material can be pre-surface treated by applying photoelectromagnetic energy. The pre-surface treatment can burn the impurities contained in the active material in a short time, form a stable oxide layer on the surface of the active material, and improve the wettability to the electrolyte by changing the surface energy of the active material.

[0044] On the other hand, by applying the photoelectromagnetic energy, the lithium salt reacts with the active material, and the gas product of the reaction flows out to the outside and generates pores. The generated pores allow lithium ions to diffuse into the active material.

[0045] Macromolecule can be used without restriction, as long as it can encapsulate active substances.For example, the macromolecule applicable to the present invention may include polyacrylonitrile (PAN), polytetrafluoroethylene (PTFE), polymethyl methacrylate (PMMA), poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS), polydiacetylene (PDA), polypropylene (PP), polystyrene (PS), polyurethane (PU), polyethylene oxide (PEO), polyethylene terephthalate (PET), styrene-ethylene-butylene-styrene (SEBS), glycerol, sucrose, cellulose, lignin, polyvinylidene fluoride (PVDF), polyvinylidene fluoride-trifluoroethylene (PVDF-TRFE), polyaniline and polyparaxylene (Parylene-C) One or more, but is not limited thereto. If more than two kinds of macromolecules are included, multiple macromolecules with different boiling points can be used, or multiple macromolecules such as carboxymethyl cellulose (CMC) and polyacrylic acid (PAA) combinations form double network hydrogels.

[0046] In another example, the polymer can be an organosilicon polymer containing negative electrode active material components inside, such as polysiloxane, polysilsesquioxane, polycarbosiloxane, polyborosilane, polysilicon cyanamide, etc. The negative electrode active material components inside the polymer can provide additional energy capacity to the electrode and can also provide additional pre-lithiation sources. By carbonizing the organosilicon polymer containing the negative electrode active material components, a shell composed of silicon oxycarbide (SiOC), silicon carbide (SiC), silicon boron carbon nitride (SiBCN), silicon carbon nitride (SiCN), etc. can be formed.

[0047] On the other hand, photo-electromagnetic energy can be applied during the mixture formation step. In this way, partial pre-lithiation of active materials and carbonization of polymers can be performed.

[0048] Furthermore, depending on the type of lithium salt and the polymer used for encapsulation, the polymer can react with lithium salts such as LiOH, LiCl, and LiF. In this case, lithium ions remain in the polymer after lithium metallization and react with the negative electrode active material when energy is applied. However, the reaction in the lithium metal state may be slower than the reaction in the lithium salt state, or more energy may be required.

[0049] In the powder drying step, the liquid mixture is sprayed by various spraying methods to form droplets, and then the solvent is removed by powder drying. The powder drying step can be performed in an air suspension chamber where the droplets can be suspended and circulated while the powder is dried. Figure 1 As shown, the powder material formed by the powder drying step may be composed of an active material 110 and a polymer layer 130 surrounding the active material, wherein the polymer layer 130 contains a lithium salt 120. A small amount of an oxide layer 115 may be formed on the surface of the active material 110.

[0050] Specifically, the powder drying step may include the following steps: spraying the liquid mixture into an air-suspended chamber by using methods such as Collison nebulization, piezoelectric spray, ultrasonic spray or electrospray to generate droplets with a size of several hundred nm to several μm; Figure 3 The heater shown suspends and circulates the droplets in the air suspension chamber and dries or Figure 6 The samples were rapidly frozen using nitrogen and then dried in vacuo.

[0051] Figure 2 An example of the electrospray method is briefly shown.

[0052] In order to produce a powder of individually encapsulated active substances, it is necessary to produce a plurality of microparticles of the mixture before drying and applying energy.

[0053] exist Figure 2 , it is exemplarily shown that the active material is encapsulated in the polymer binder and sprayed in the form of droplets 210 by electrospraying using a Collison sprayer 201 .

[0054] The Collison nebulizer was originally developed by KR May in 1972 [May 1972] and has long been recognized as a technology for aerosolizing a variety of liquids. In the Collison nebulizer, air is moved at high speed through the small holes of the nebulizer, after which liquid is sucked from the nebulizer jar and broken into small droplets. The sprayed liquid then strikes the jar wall, generating even smaller droplets. Larger particles are removed from the aerosol by an arc-shaped discharge tube.

[0055] and Figure 2 Unlike the examples shown, both piezoelectric sprayers and ultrasonic sprays use piezoelectric transducers to generate the particles of the spray. If a high-frequency voltage is applied to the transducer, the transducer will generate high-frequency vibrations. In an ultrasonic sprayer, a liquid is placed on the surface of a piezoelectric transducer, and vibrations are applied to the liquid through the transducer. The vibrations form capillary waveforms (standing waves) in the liquid, in which small droplets are released from the liquid in the form of an aerosol. In ultrasonic spray, the liquid is sprayed when it reaches the surface of the vibrating nozzle, so the sample principle is applied. The size of the sprayed particles varies depending on the vibration frequency applied. In order to generate nanoparticles, vibrations in the frequency range of several megahertz (MHz) are required. Due to geometric limitations, ultrasonic sprayers are more commonly used in the range of several megahertz, and sprayers are limited to tens of kilohertz.

[0056] Figure 3A process for drying an active substance encapsulated in powder form in an air suspension chamber using an infrared (IR) heater is shown.

[0057] Figure 3 The powder drying system shown includes: a transparent cylindrical chamber 310; an atomic nozzle 320 for providing an encapsulated active substance 301 in the form of droplets as a drying object; an infrared heater 330 for applying heat 335 to the encapsulated active substance; and a blower 340 for continuously suspending the encapsulated active substance in the transparent cylindrical chamber 310.

[0058] In such Figure 3 In the powder drying system shown, the encapsulated active material 301 sprayed through the atomic nozzle 320 is continuously suspended in the air in a sealed transparent cylindrical chamber 310 by circulating air through a blower 340 and irradiated by an infrared (IR) heater 330 for drying.

[0059] On the other hand, Figure 4 As shown, photoelectromagnetic energy can be applied in the air suspension chamber. By applying the photoelectromagnetic energy, pre-lithiation of the active material and carbonization of the polymer can be performed. This can replace the subsequent step of applying photoelectromagnetic energy, or be performed separately from the photoelectromagnetic energy application step described later.

[0060] In the pre-lithiation and polymer carbonization step by applying photo-electromagnetic energy, photo-electromagnetic energy is applied to the dried powder product to pre-lithiate the active material and simultaneously carbonize at least a portion of the polymer surrounding the active material. In this way, for example, if the active material is silicon, the following can be obtained: Figure 1 The negative electrode material in the illustrated example includes: a lithium-silicon alloy 140 ; ​​a lithium silicate salt 145 as a lithium-silicon oxide; and a carbon film 135 including pores 138 .

[0061] The photoelectromagnetic energy that can be used in the present invention is intense pulsed light (IPL) or microwave.

[0062] In the application of photoelectromagnetic energy, the application of intense pulsed light (IPL) is carried out by irradiating high-power xenon light. On the other hand, different carbonization effects of polymers can be achieved according to the application time of intense pulsed light (IPL). For example, according to the application of intense pulsed light (IPL) within 5 milliseconds, the carbonization effect is mainly concentrated on the outside of the shell, and a shell structure including a hard carbonized outer shell and a soft inner shell in an inner polymer state is obtained. For example, by applying intense pulsed light (IPL) for more than 5 milliseconds, the polymer is carbonized as a whole, and a shell formed entirely of carbon can be obtained.

[0063] By applying photoelectromagnetic energy, the nanoporous shell based on the evaporation of low-boiling-point polymers and solvents makes lithium diffusion easier, and the carbonized outer shell can provide structural strength. If there is an inner shell of uncarbonized polymers, it can provide an elastic and deformable space for the volume change of the active material during the lithiation process.

[0064] The carbonized outer shell or carbonized shell provides conductivity and structural support according to the solid electrolyte interface (SEI). The inner layer of the soft polymer has elasticity and provides space for the volume expansion of the active material without being crushed.

[0065] For microwave application, a partially carbonized or entirely carbonized shell can also be formed depending on the power or time.

[0066] On the other hand, after the photo-electromagnetic energy application step, the powdered negative electrode material may be further refined by a known milling method such as ball milling or jet milling.

[0067] The pre-lithiation of negative electrode active materials such as silicon based on the application of photoelectromagnetic energy forms Li by reacting the active material with lithium salt under high temperature (e.g., above 200°C). x Si and / or Li x SiO y Lithiated active material particles.

[0068] The method of the present invention pre-lithiates the active material in powder form by applying photoelectromagnetic energy treatment to the lithium salt and reducing the lithium by thermal reduction. When a metal having a larger free energy change of oxidation reaction than lithium is used, the lithium is reduced and the metal is oxidized. For example, when Si metal, which is a negative electrode material, is used as a reducing agent, lithium salts such as lithium oxides can be reduced to lithium metal by applying photoelectromagnetic energy such as intense pulsed light (IPL), thereby generating a lithium-silicon alloy (Li x Si) and / or lithium silicate (Li x SiO y ) and other pre-lithiated Si particles.

[0069] Figure 4 An example of applying intense pulsed light (IPL) to an active substance encapsulated in powder form within an air suspension chamber is schematically shown.

[0070] Since IPL application can irradiate a larger surface area with IPL at one time, it can be considered as a more suitable energy application method for encapsulated active substances in powder form. In addition, the pulse duration of a common IPL system is several milliseconds, and the energy density that can be released is 12 J / cm 2When considering ordinary IPL systems, the diffusion depth of IPL irradiation is limited to about 1 μm below the surface, and therefore, it is more suitable for active material processing in powder form.

[0071] Reference Figure 4 In order to uniformly irradiate the energy of the intense pulsed light (IPL) 435 to the encapsulated active material powder 401, a specially designed chamber 410 is used, and a blower 440 is used to suspend the dry encapsulated active material powder 401 in the air. The chamber 410 is made of a light-transmitting material (glass or transparent polycarbonate, etc.). The blower 440 suspends the encapsulated active material 401 in the air by continuously blowing. The intense pulsed light (IPL) lamp 430 uses a xenon lamp and is set in a manner facing the chamber 410. In order to irradiate all surfaces of the active material particles in the intense pulsed light (IPL) process, the other side of the chamber 410 is covered by a reflective plate 420.

[0072] like Figure 1 In the example shown, the negative electrode material for a lithium secondary battery in an embodiment of the present invention may be a powder comprising a lithiated active material and a shell layer surrounding the lithiated active material and having pores. The lithiated active material includes a lithium-silicon alloy and a lithium silicate layer surrounding the lithium-silicon alloy. The outermost side of the shell layer may be formed of carbon.

[0073] At least the outermost shell layer formed of carbon can contain one-dimensional or two-dimensional carbonaceous materials such as carbon nanotubes and / or graphene oxide, which can improve the absorption of electromagnetic wave energy in a wider wavelength range and also improve the conductivity of the generated negative electrode material.

[0074] In lithium secondary batteries, the first charge process is critical to battery performance. During the first charge, the organic electrolyte may undergo a reduction reaction to form a solid electrolyte interface on the negative electrode surface, or a portion of the lithium ions may be captured by the electrode during the first lithiation process. This may lead to irreversible loss of the net energy capacity of the battery. The first cycle is particularly important when silicon, which undergoes a large volume change during charge and discharge, is used for the negative electrode.

[0075] In the present invention, the loss of energy density in the first charging cycle can be compensated by achieving pre-lithiation of the active material in the method described.

[0076] Figure 5 The charge and discharge process of the negative electrode material for a lithium secondary battery of the present invention is briefly shown.

[0077] Silicon and silicon oxide negative electrode active materials can be pre-lithiated to form a lithium-silicon alloy 510. A lithium silicate layer 520 and a carbon layer 530 including a plurality of pores can be formed on the surface of the lithium-silicon alloy 510. Through the pre-lithiation of the negative electrode active material, during discharge, the lithium component flows out from the negative electrode from the initial stage of battery operation, forming the form of silicon 550 and a silicon oxide layer 560, and a space 540 is formed between these and the carbon layer. The lithium component enters the negative electrode during charging. This charging and discharging process can be made easier by the plurality of pores on the surface of the negative electrode material. In the present invention, the shell formed by the solid carbon is lithiated to conform to the volume of the expanded active material, that is, to surround the active material so that the space 540 is maintained during discharge, so that the structure of the negative electrode active material may not be broken due to the volume change of silicon during the subsequent charging and discharging process.

[0078] Figure 6 An example of an apparatus for drying an active substance encapsulated in a powder form using a spray freeze drying method is briefly shown.

[0079] Figure 6 The spray freeze drying system shown includes: a transparent cylindrical chamber 610; an atomic nozzle 620 for providing an encapsulated active substance 601 in the form of droplets; a nitrogen spray device 630 having a plurality of nozzles 635 for freezing the encapsulated active substance 601; and a vacuum section 640 having a filter and a vacuum pump for continuously drying the encapsulated active substance in the transparent cylindrical chamber 610.

[0080] If using Figure 6 In the device shown, the liquid mixture is sprayed into the chamber to generate droplets, and nitrogen is used to quickly freeze the plurality of droplets into frozen powder, which can be vacuum dried.

[0081] go through Figure 6 The freeze drying step shown is followed by the encapsulated active substance powder in Figure 4 Carbonization is performed in an air suspension device by intense pulsed light (IPL) or microwave irradiation.

[0082] The above description is centered on the embodiments of the present invention, but a person skilled in the art may make various modifications or variations. Therefore, as long as such modifications and variations do not depart from the scope of the present invention, it can be understood that these modifications and variations are included in the scope of the present invention.

Claims

1. A method for producing a negative electrode material for a lithium secondary battery, characterized in that: The steps include: mixing the active material, the polymer and the lithium salt in a solvent to form a liquid mixture; Drying the liquid mixture into powder; and Photo-electromagnetic energy is applied to the powder dried product to pre-lithiate the active material and carbonize at least a portion of the polymer.

2. The method for producing a negative electrode material for a lithium secondary battery according to claim 1, characterized in that: The active material includes at least one of silicon and silicon oxide.

3. The method for producing a negative electrode material for a lithium secondary battery according to claim 1, characterized in that: The active material is previously surface treated by applying photo-electromagnetic energy.

4. The method for producing a negative electrode material for a lithium secondary battery according to claim 1, characterized in that: By applying the photoelectromagnetic energy, the lithium salt reacts with the active material, and the gas product of the reaction flows out to the outside to generate pores.

5. The method for producing a negative electrode material for a lithium secondary battery according to claim 1, characterized in that: The lithium salt includes one or more of Li2O, LiOH, LiO2CH, Li2CO3, Li2C2O4, Li3C6H5O7, LiNO3, LiCl, LiF or lithium-functionalized polymers.

6. The method for producing a negative electrode material for a lithium secondary battery according to claim 1, characterized in that: The solvent includes an aqueous solvent or an organic solvent.

7. The method for producing a negative electrode material for a lithium secondary battery according to claim 1, characterized in that: The step of drying the powder comprises the following steps: spraying the liquid mixture into an air suspension chamber to generate droplets; and The droplets are circulated and dried in the air suspension chamber by using a heater.

8. The method for producing a negative electrode material for a lithium secondary battery according to claim 7, characterized in that: Optical and electromagnetic energy is applied within the air suspension chamber.

9. The method for producing a negative electrode material for a lithium secondary battery according to claim 1, characterized in that: The step of drying the powder comprises the following steps: spraying the liquid mixture into the chamber to generate droplets; rapidly freezing the liquid droplets into a frozen powder in the chamber using nitrogen gas; and The frozen powder was vacuum dried.

10. A negative electrode material for a lithium secondary battery, characterized in that: include: lithiated active material; and The shell layer surrounds the lithiated active material and is formed with pores. The lithiated active material comprises a lithium-silicon alloy and a lithium silicate layer surrounding the lithium-silicon alloy. The outermost side of the shell layer is formed of carbon.

11. The negative electrode material for lithium secondary battery according to claim 10, characterized in that: The entire shell layer is formed of carbon.

12. The negative electrode material for lithium secondary battery according to claim 10, characterized in that: The shell layer comprises: an outer shell formed of carbon; and The inner shell is formed by polymer.